Voting for Health Insurance Policy: the U.S. versus Europe - Xinwen Ni (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2019)
In this paper, we build an overlapping generation model to examine the reason why developed countries with similar background have implemented different social health insurance systems. We propose two hypotheses to explain this phenomenon: (i) the different participation rates of the poor in the voting; (ii) the distinct attitudes towards the size of the government and the existence of a compulsory social health insurance system. Agents need to vote for one of two policies: Policy I without Social Health Insurance (SHI) but with the subsidy for the poor, and Policy II with fully covered SHI. By comparing either their current utility or the expected life time utility, households will choose one policy. We find that under Policy I, the derivative of the changes of expected utility with respect to income is not monotonic. This means that both the poorest and the richest dislike the social health insurance system. With the calibrated parameters, we solve the benchmark and find that the public's attitude towards the size of the government and the lower representation of the poor affect the election result. The changes in the minimum consumption level under Policy I affect the voting results most, followed by the attitude. Voting Participant rate plays the most insignificant role in the voting outcome. The sensitivity analysis shows that our main findings are robust to the input parameters.
Keywords: C00; 330; Social Health Insurance; Voting